The Immune Pathogenesis of Acute-On-Chronic Liver Failure and the Danger Hypothesis - Qiang, Rui; Liu, Xing-Zi; Xu, Jun-Chi (Frontiers in Immunology, 2022)
Acute-on-chronic liver failure (ACLF) is a group of clinical syndromes related to severe acute liver function impairment and multiple organ failure caused by various acute triggering factors on the basis of chronic liver disease. Due to its severe condition, rapid progression and high mortality, it has received increasing attention. Recent studies have shown that the pathogenesis of ACLF mainly includes direct injury and immune injury. In immune injury, CTLs, DCs and CD4+ T cells accumulate in the liver tissue, secrete a variety of proinflammatory cytokines and chemokines, and recruit more immune cells to the liver, resulting in immune damage to the liver tissue, massive hepatocyte necrosis and liver failure, but the key molecules and signaling pathways remain unclear. The “danger hypothesis” holds that in addition to the need for antigens, damage-associated molecular patterns (DAMPs) also play a very important role in the occurrence of the immune response, and this hypothesis is related to the pathogenesis of ACLF. In this paper, the research status and development trend of ACLF, as well as the mechanism of action and research progress on various DAMPs in ACLF, are summarized to find biomarkers that can predict the occurrence and development of diseases or can predict the prognosis of patients early on.